An Analysis of the Efficiency of Enjoyment the Right to Health in Uganda - Jackson Philip Wabwire (Uganda Christian University, 2025)
This dissertation examines the efficiency of the enjoyment of the right to health in Uganda. It delves into both legal and non-legal aspects of its realization. Embedded in national, regional and international legal frameworks, the study evaluates Uganda’s Constitutional and legislative commitments and its obligations under ratified human rights treaties. The research utilizes doctrinal and qualitative methods, drawing from statutes, case law, academic literature, and international instruments to assess both enforcement mechanisms and judicial trends. Through a critical analysis of landmark cases and practical shortcomings that undermine health rights in Uganda. The dissertation concludes with strategic recommendations for legislative reform, institutional accountability and enhanced community engagement, aimed at strengthening the legal protection and practical accessibility of health services for all Ugandans.
THESIS